Modelo de intervención psicoeducativa en niños con autismo del cantón Montalvo de la Provincia de Los Ríos - Balseca Zúñiga, Alex Josué (2023)
The present research is aimed at proposing a psychoeducational intervention model for children with autism in the Leopoldo Zumba Educational Unit of the Montalvo Canton, province of Los Ríos. Therefore, it is important to describe basic concepts about what autism is, its incidence, evaluation and research techniques such as structured interviews, psychometric tests and inventories used for this research project, through a Mixed methodology with bibliographic and analytical techniques. , descriptive, inductive-deductive and psychometric, to guide the research in an organized, objective and scientific way, the present research being a non-experimental design, once the results have been analyzed and reasoned, the suggestion of a psychoeducational model adapted to the needs will be proposed. specific to the condition of the children evaluated that will promote the orientation, development and learning of children with ASD.